The roles and applications of additive manufacturing in the aerospace and automobile sector. (2021) - Mohanavel, V.; Ashraff Ali, K.S.; Ranganathan, K.; Allen Jeffrey, J.; Ravikumar, M.M.; Rajkumar, S.
Abstract: Additive manufacturing or 3D printing is one of the developing technologies of the manufacturing field. 3D printing is establishing its power and potential in various areas by implementing new processing techniques of 3D printing over the world. 3D Printing is proving its efficiency in fabricating 3D models, especially in aerospace, automobile, medical etc. The existing and non-existing components in various fields can be produced by scanning or designing the particular components through designing software. We can print them through a 3D printer. Using additive manufacturing, we can make stronger and light-weighted products within a short period. The components can also be manufactured through various plastic and metal materials. Rapid prototyping is one of the time-saving processes of 3D printing in the aerospace and automobile industries. Nowadays, 3D printing is developing to solve human health issues by printing the human organs through the tissues of a particular human. It is a time-saving and cost-efficient technique. If we compare the other traditional manufacturing techniques with additive manufacturing, AM is environmentally friendly to both nature and humans. The safety provided by the AM products is also well and good. Raw material wastages can be prevented. Here we review the topics regarding additive manufacturing techniques, 3D printing in the automobile and aerospace field.